Potensi Ekonomi Sumber Daya Kelautan Wilayah Pesisir Kabupaten Langkat Dalam Mencapai Blue Economy - Sri Endang Rahayu; Prawidya Hariani RS; Elizar Sinambela (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2022)
Blue Economy is a future economic model activity that considers advantages and innovation strategies by following the natural conditions of the coast. Blue Economy is also a tool that can be used to improve unfavorable economic conditions and create more activities with an activity model that must be sustainable. The concept of sustainable development is one of the efforts to preserve the environment. Indonesia strongly supports the implementation of the concept of sustainable development, one of which is the Blue Economy concept. As a maritime country (blue economy), Indonesia's biodiversity is very large and must be managed more efficiently and effectively, so that the economy of coastal communities in the future will be better.This study aims to analyze the economic potential of coastal marine resources in achieving the Blue Economy concept in Langkat Regency, Sumatra Utara province. The contribution of the fisheries and marine sectors has increased, followed by the development of mangrove forest-based village tourism. However, the potential in the mangrove area has not been achieved optimally because the economic use of the results of the mangrove ecosystem has not been economically exploited. Therefore the economic level of the community in the coastal area of Langkat Regency is still relatively low and has not been able to develop other sectors based on coastal ecosystems. The development of technology and industrialization in the economy today are two things that are contradictory to the preservation of the natural environment around the world because the drive to improve the economy produces a lot of natural damage associated with unsustainable development. Consequently, the development of the economic sector becomes a strong challenge for the world economy by using a system that tends to be exploitative. The pattern of planning and management of the marine and fisheries sector must be reflected in the RPJMD and the strategic plan for Langkat Regency.